THE INFLUENCE OF E-SERVICE QUALITY , E-TRUST , AND E-SATISFACTION ON E -LOYALTY IN THE GO-JEK APPLICATION - Supriyatin SY (Jurnal Ekonomi, 2021)
This research was conducted with the intention of determining the impact that E-Service Quality, E-Trust, and E-Satisfaction have on E-Loyalty in relation to the Gojek application. This inquiry is a quantitative study that employs descriptive statistical calculations using SPSS version 26.0 and an associative methodology. According to this investigation's findings, there is a correlation between high levels of e-service quality and e-loyalty. On the other hand, e-satisfaction has a large influence on e-loyalty, whereas e-trust has no significant influence on e-loyalty. Consequently, it is feasible to conclude that there is a relationship between the degrees of e-service quality, e-satisfaction, and e-loyalty. E-Service Quality, E-Trust, and E-Satisfaction all have a strong and relevant influence on E-Loyalty.